Counseling couples in conflict : a relational restoration model - Sells, James Nathan, 1958-; Yarhouse, Mark A., 1968-; Christian Association for Psychologcal Studies (Downers Grove, Ill. : IVP Academic, 2011)
Most therapeutic approaches, especially those of a cognitive orientation, are not very effective in dealing with high conflict relationships--couples often heading toward divorce by the time they seek help. Counseling Couples in Conflict is a resource for counselors and therapists who want to be ready for these difficult cases. Utilizing a relational conflict and restoration model Mark Yarhouse and James Sells point the way beyond the cycle of pain towards marital healing. --from publisher description.
Marriage at a crucial stage of existence -- Three fights in one -- Marriage is an us -- Pastoral and counseling boundaries: invested but not overinvolved -- Pain and defense -- Offense and injury -- Grace and justice -- Empathy and trust -- Forgiveness -- The expressive art of sexuality -- The product of art: children and parenting -- Sexual infidelity -- Divorce and blended families -- Substance abuse and behavioral addictions -- A graceful conclusion.
Includes bibliographical references and index.
Keywords: Marriage counseling; Pastoral counseling; Counseling -- Religious aspects -- Christianity; Counseling -- Religious aspects -- Christianity; Marriage counseling; Pastoral counseling